THE RELEVANCE OF ISLAMIC RELIGIOUS EDUCATION MATERIALS TO STUDENTS' SOCIAL AND EMOTIONAL INTELLIGENCE - Elik Cahyaning Devikawati; Hanifudin; Asriana Kibtiyah; Rofiatul Hosna (Program Studi Manajemen Pendidikan Islam, 2026)
This study aims to analyze the contribution of Islamic Religious Education materials in developing the social and emotional intelligence of fourth grade elementary school students. The novelty of the study lies in analyzing the relevance of PAI material content to students social emotional behavior, not just the method or cognitive learning outcomes. This research method uses a qualitative approach with a phenomenological approach. Data collection was conducted through learning observations, in depth interviews with PAI teachers and students, and analysis of curriculum documents and learning tools. The results of the study indicate that 1) Islamic Religious Education (PAI) materials in fourth grade elementary school at SD Negeri 1 Kaumrejo are implemented in a planned and contextual manner, emphasizing the internalization of values through role models, habituation, and strengthening students religious attitudes and social behavior 2) students social and emotional intelligence develop quite well, characterized by the ability to cooperate, empathize, mutual respect, and manage emotions, although guidance is still needed in emotional control and conflict resolution 3) PAI materials have strong relevance to the development of students social and emotional intelligence, because their consistent and reflective implementation contributes significantly to shaping positive social behavior and strengthening the role of PAI in character education in elementary schools